2010
DOI: 10.1186/1743-8977-7-4
|View full text |Cite
|
Sign up to set email alerts
|

Inflammogenic effect of well-characterized fullerenes in inhalation and intratracheal instillation studies

Abstract: BackgroundWe used fullerenes, whose dispersion at the nano-level was stabilized by grinding in nitrogen gas in an agitation mill, to conduct an intratracheal instillation study and an inhalation exposure study. Fullerenes were individually dispersed in distilled water including 0.1% Tween 80, and the diameter of the fullerenes was 33 nm. These suspensions were directly injected as a solution in the intratracheal instillation study. The reference material was nickel oxide in distilled water. Wistar male rats in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
57
0
6

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 64 publications
(66 citation statements)
references
References 29 publications
3
57
0
6
Order By: Relevance
“…10 However, some studies have shown that NiONP exposure induces only mild and reversible inflammation. 33,34 Zhang et al 35 found that NiO (20 µg suspended in 50 µL of PBS) exposure induced less neutrophil cell counts, monocyte chemotactic protein-1, and IL-6 levels in BALF compared with the same amount of CuO and Cr 2 O 3 exposure in C57 BL/6 mice. We suppose that the discrepancy in these results may be due to the different properties and the ability to induce oxidative stress of NPs.…”
mentioning
confidence: 99%
“…10 However, some studies have shown that NiONP exposure induces only mild and reversible inflammation. 33,34 Zhang et al 35 found that NiO (20 µg suspended in 50 µL of PBS) exposure induced less neutrophil cell counts, monocyte chemotactic protein-1, and IL-6 levels in BALF compared with the same amount of CuO and Cr 2 O 3 exposure in C57 BL/6 mice. We suppose that the discrepancy in these results may be due to the different properties and the ability to induce oxidative stress of NPs.…”
mentioning
confidence: 99%
“…Inhalation exposure studies of C 60 on mice and rats have also taken place by Yokoyama et al 51) and Morimoto et al 50) . Using the same dispersed fullerene suspension as used in the intratracheal instillation study, Shimada et al 52) succeeded in stabilizing the particle concentration and nanoscale sizes of airborne fullerenes with a pressurized nebulizer.…”
Section: Fullerenesmentioning
confidence: 98%
“…The second step involves the estimation of the acceptable exposures of TiO 2 nanomaterials for humans by extrapolating the NOAEL for experimental animals to humans taking into consideration the uncertainty factor (UF), which will be described later (2 a positive control, but not that of C 60 51) . Furthermore, Morimoto et al 50) exposed Wistar rats to 0.12 mg/m 3 C 60 aerosol (mean geometric diameter, 96 nm; particle concentration, 4.1 × 10 4 /cm 3 ) for 6 h/day, 5 days/wk for 4 wk, followed by 3 mo observation. In the lungs there was only slight transient inflammation.…”
Section: Fullerenesmentioning
confidence: 99%
See 2 more Smart Citations